2015
DOI: 10.1007/s00256-015-2146-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and first validation of a simplified CT-based classification system of soft tissue changes in large-head metal-on-metal total hip replacement: intra- and interrater reliability and association with revision rates in a uniform cohort of 664 arthroplasties

Abstract: The presented simplified CT grading system (A-C) in its first clinical validation on 48- and 64-multislice systems is reliable, showing good intra- and interrater reliability and is independently associated with revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In addition, an investigation of the effect of the severity of disease on these variables demonstrated that the amount of bleeding and duration of operation increased as the grade increased according to the CT classification. This study also showed that the CT-based classification described by Boomsma et al [10] was useful in evaluating PT as it seems to correlate with difficulties in its excision.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In addition, an investigation of the effect of the severity of disease on these variables demonstrated that the amount of bleeding and duration of operation increased as the grade increased according to the CT classification. This study also showed that the CT-based classification described by Boomsma et al [10] was useful in evaluating PT as it seems to correlate with difficulties in its excision.…”
Section: Discussionsupporting
confidence: 68%
“…Patients' preoperative hemoglobin values and bearing surfaces were reported in Table II. Pseudotumors characteristics were classified according to preoperative imaging, using both MRI [11] and CT [10] (Table II, Figure 1).…”
Section: Thismentioning
confidence: 99%
See 2 more Smart Citations
“…These are non-neoplastic and non-infective lesions situated in various locations in the peri-prosthetic tissue. 31,32 A pseudotumour is referred to more specifically as an adverse reaction to metal debris (ARMD), and more generally as an adverse local tissue reaction (ALTR). The term ‘aseptic lymphocytic vasculitis-associated lesion’ (ALVAL) is reserved for histological findings; 33 the term ‘metallosis’ should be avoided for these cases.…”
Section: Local Tissue Reactionsmentioning
confidence: 99%